The monocyte-dependent immune response to bacteria is suppressed in smoking-induced COPD - Knobloch, Jürgen; Panek, Susanne; Yanik, Sarah Derya; Jamal Jameel, Kaschin; Bendella, Zeynep; Jungck, David; Bürger, Paul; Bülthoff, Eike; Struck, Birte; Giannakis, Nikolaos; Rupp, Jan; Kronsbein, Juliane; et al. (Journal of molecular medicine (Berlin, Germany), 2019)
COPD patients have an increased susceptibility to bacterial airway infections that can induce exacerbations. In response to infections, circulating monocytes become recruited to the infected tissue and secrete cytokines. We hypothesized that this cytokine response is reduced in COPD. Cultured peripheral blood monocytes of never smokers (NS) and smokers without (S) and with COPD (3 study populations, n = 36–37) were stimulated with extracts of Haemophilus influenzae , Staphylococcus aureus , or Streptococcus pneumoniae or with four different pathogen-associated molecular patterns (PAMPs). Four cytokines and 9 PAMP-related signaling molecules were measured and compared between the groups. Granulocyte-macrophage-colony-stimulating-factor responses to all stimulants were reduced in S and COPD compared to NS. Tumor-necrosis-factor-α responses to all bacterial extracts, peptidoglycan, and lipopolysaccharide were reduced in S and/or COPD. Interleukin-10 responses to S. aureus and lipoteichoic acid were increased in COPD. Correlations to pack-years and lung function were found. The peptidoglycan-receptor NOD2 and the mRNA of the lipopolysaccharide-receptor TLR4 were reduced in S and COPD. Cytokine responses of monocytes to bacteria are suppressed by smoking and in COPD possibly due to NOD2 and TLR4 reduction and/or interleukin-10 increase. This might help to explain the increased susceptibility to bacterial infections. These systemic molecular pathologies might be targets for therapeutic strategies to prevent infection-induced exacerbations. Key messages COPD subjects have an increased susceptibility to bacterial infections. This implies defects in the immune response to bacteria and is critical for disease progression. The cytokine response of monocytes to bacteria is reduced in COPD. This might be due to a reduced NOD2 and TLR4 and an increased IL-10 expression. This can explain the increased susceptibility to infections and help to identify drug targets.